Efisiensi Biaya Produksi IPA Syarkawi Menggunakan Poly Aluminium Chloride (PAC) Dengan Metode Anova - Rahman, Faisal (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
The clean water needs of the community, both domestic and industrial, in the cities of Banjar and Banjarbaru Regency are provided by the Intan Banjar Regional Drinking Water Company in collaboration with PT. Drupadi Tirta Intan who uses the Martapura river as a source of raw water. PAC is a coagulant commonly used in water treatment. PAC influences the size of production costs. This research aims to obtain PAC chemicals that are effective, efficient and in accordance with the characteristics of PT Drupadi Tirta Intan's WTP, so that Syarkawi WTP operators can easily operate the IPA using PAC chemicals when raw water turbidity is high or low. The chemical application process is good, namely the Jartes and Plant Test processes. To compare the parameters of the Jartes test and plant test, the author used the statistical method Analysis of Variance (ANOVA) to find out whether the two products had good performance. From the research results, it was found that both PAC products from PT A and PT B could be used as coagulants for the Syarkawi IPA Water Treatment Plant unit, however the level of effectiveness and price efficiency of the products from PT B was better.